Prediction of Drag Reduction in Slickwater Fracturing by Two General Models - Chen, Pengfei; Chang, Honggang; Fu, Yongqiang; Tang, Yongfan; Huang, Xuesong; Yu, Weichu (Frontiers in Energy Research, 2022)
Slickwater fracturing is an evolving and enabling technology for shale gas development. Due to its high injection rate, drag reduction (DR) is critical to the success of the hydraulic fracturing operation with slickwater. This paper presents two novel general models to predict the field drag reduction based on the dynamic similarity. For general model 1, as long as the Reynolds numbers (Re) of laboratory and field were same, the DR can be predicted by Where, Q is the volumetric flow rates, D is pipe diameters, and ∆P is pressure drop.The validation of model 1 by comparing the laboratory result and field tests shows high accuracy with uncertainty in the range of -10% to 10%. General model 2 is easier than model 1, the DR can be predicted by It gives results with an error range of -6% to 6%. The two novel general models have a much broader scope of application than that of reported models.